Peningkatan Fasilitas Pelayanan Penumpang Kereta Api Di Stasiun Sepanjang Daop 8 Surabaya - Hermawan, Azhar; Nursabrina, Annisa; Purwatiningsih, Purwatiningsih (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2021)
Regional Operation 8 Surabaya is one of the operating areas located in the working area of the Railway Engineering Hall of East Java Region. Sepanjang Station is one of the medium-class stations located on the Wonokromo-Mojokerto cross and at this time the condition of the facility is not in accordance with minimum service standards in The Minister of Transportation Regulation Number PM 63 of 2019 and the technical standards of station building in The Minister of Transportation Regulation Number PM 29 of 2011. Therefore, improvements in passenger service facilities to fulfill the right of passengers as consumers to receive services in accordance with their standards. This research uses field survey methods by observing directly to find out the existing conditions of the Sepanjang Station, as well as surveying passengers in rush hour to find the number of passengers at the station at certain hours of the day. The observations obtained that the passenger service facilities at Sepanjang Station are still not in accordance with the standards of medium-class stations. There are several passenger service facilities that need to be improved. Because a high level of safety, security and comfort can be achieved if the infrastructure conditions are in good condition, for that the feasibility factor of station infrastructure is very influential in the implementation of fast and safe rail transportation.